Phytochemical and Therapeutic Potential of (L.) Osbeck: A Review - Rusat Jahin Anmol M. Pharm; Shabnam Marium M. Pharm; Fei Tsong Hiew PhD; Wan Chien Han BSc (Hons.); Lee Kuan Kwan BSc (Hons.); Alicia Khai Yeen Wong PhD; Farzana Khan M. Pharm; Md. Moklesur Rahman Sarker PhD; Siok Yee Chan PhD; Nurolaini Kifli PhD; Long Chiau Ming PhD (SAGE Publishing, 2021)
Citrus grandis or Citrus maxima , widely recognized as Pomelo is widely cultivated in many countries because of their large amounts of functional, nutraceutical and biological activities. In traditional medicine, various parts of this plant including leaf, pulp and peel are used for generations as they are scientifically proven to have therapeutic potentials and safe for human use. The main objective of this study was to review the different therapeutic applications of Citrus grandis and the phytochemicals associated with its medicinal values. In this article different pharmacological properties like antimicrobial, antitumor, antioxidant, anti-inflammatory, anticancer, antiepileptic, stomach tonic, cardiac stimulant, cytotoxic, hepatoprotective, nephroprotective, and anti-diabetic activities of the plant are highlighted. The enrichment of the fruit with flavonoids, polyphenols, coumarins, limonoids, acridone alkaloids, essential oils and vitamins mainly helps in exhibiting the pharmacological activities within the body. The vitamins enriched fruit is rich in nutritional value and also has minerals like calcium, phosphorous, sodium and potassium, which helps in maintaining the proper health and growth of the bones as well as the electrolyte balance of the body. To conclude, various potential therapeutic effects of Citrus grandis have been demonstrated in recent literature. Further studies on various parts of fruit, including pulp, peel, leaf, seed and it essential oil could unveil additional pharmacological activities which can be beneficial to the mankind.